PENYULUHAN PENANGANAN ARTHRITIS PADA LANSIA DI DESA MEKARMUKTI SINGAJAYA - Susan Susyanti; K Dewi Budiarti; Iin Patimah; N. Ai Erlinawati (LP4M STIKes Karsa Husada Garut, 2021)
The increasing number of population and the life expectancy of the elderly will cause various problems, including health, psychological, and socio-economic problems. Problems in the elderly are mostly health problems due to the aging process, plus other problems such as financial problems, loneliness, feeling useless, and unproductive. The purpose of this counseling is to describe the characteristics of the respondents, the history of accompanying diseases and the types of rheumatic diseases in the elderly in Mekarmukti Singajaya. Method The approach to problem solving is to build partnerships with elderly groups in posyandu and recitation programs in the work area of the Singajaya Public Health Center. To foster this partnership, counseling was conducted on the management of rheumatoid arthritis pain in the elderly at home. The team consists of lecturers and is assisted by STIKes KHG Nursing S1 students. The results obtained from this counseling, the elderly can apply pain management at home by compressing. The elderly were very enthusiastic about participating in the counseling. This is evidenced by the fact that there are 10 elderly people who ask about rheumatoid arthritis and the elderly can apply warm compresses. So it can be concluded that it is very important to carry out counseling about the management of rheumatoid arthritis pain in the elderly. So that the elderly know how to manage pain in order to improve the health status of the elderly.